"Subliminal accent": Reactions to the rise of Wisconsin English. Issue 1 (6th December 2016) - Schuld, Danielle; Salmons, Joseph; Purnell, Thomas; Raimy, Eric
Abstract : Distinctive regional varieties of English have only recently emerged in parts of North America, including Wisconsin, where differences appear to be increasing today. We present an experiment in which listeners heard two short samples each from three Wisconsin regions and three other dialect areas. For each area, one sample was recorded pre-1970 and another recorded post-2010. Regional stereotypes were excluded. In a situation of new and still-emerging regional varieties, we expected listeners to be able to more accurately identify recent speech samples versus old samples from Wisconsin. Listeners proved better at recognizing speakers from Wisconsin in newer over older recordings. This complicates previous discussions of dialect awareness, in particular 'enregisterment, ' with our listeners able to identify Wisconsin speech even in the absence of salient, known dialect features.